Dependence of quality on the completed standard x-ray dental installations on the diagnostic process - V. P. Truten; O. Ya. Lubasheva (Эндодонтия Today, 2020)
The article is devoted to determining the dependence of the quality of performance by an x-ray laboratory technician and, especially, by the dental assistant, of standard x-ray dental laying on the process of examining teeth and jaws. A retrospective analysis of 900 intraoral radiographs, orthopantomograms, enlarged panoramic radiographs in direct projection (analog and digital, performed in various medical facilities) of patients in the age group of 18-85 years was performed. The most signfTcant methodological errors of the paramedical staff (especially dental assistants) of the X-ray room were determined, which lead to the appointment of a re-examination, the implementation of additional projections, auxiliary visualization techniques and an increase in the number of false-negative results.